Natural Tolerance to Ischemia and Hypoxemia in Diving Mammals: A Review - Allen, Kaitlin N.; Vázquez-Medina, José Pablo (Frontiers in Physiology, 2019)
Reperfusion injury follows ischemia/reperfusion events occurring during myocardial infarction, stroke, embolism, and other peripheral vascular diseases. Decreased blood flow and reduced oxygen tension during ischemic episodes activate cellular pathways that upregulate pro-inflammatory signaling and promote oxidant generation. Reperfusion after ischemia recruits inflammatory cells to the vascular wall, further exacerbating oxidant production and ultimately resulting in cell death, tissue injury, and organ dysfunction. Diving mammals tolerate repetitive episodes of peripheral ischemia/reperfusion as part of the cardiovascular adjustments supporting long duration dives. These adjustments allow marine mammals to optimize the use of their body oxygen stores while diving but can result in selectively reduced perfusion to peripheral tissues. Remarkably, diving mammals show no apparent detrimental effects associated with these ischemia/reperfusion events. Here, we review the current knowledge regarding the strategies marine mammals use to suppress inflammation and cope with oxidant generation potentially derived from diving-induced ischemia/reperfusion.